The Haematological Effects of Oleanolic Acid in Streptozotocin-Induced Diabetic Rats: Effects on Selected Markers - Charity M. Baloyi; A. Khathi; Ntethelelo H. Sibiya; Phikelelani S. Ngubane (Journal of Diabetes Research)
Background. Sustained hyperglycaemia leads to the development of haematological alterations which, if left untreated, is associated with cardiovascular complications. Insulin is the mainstay drug in type 1 diabetes mellitus (T1D); however, the use of insulin is associated with haematological alterations that could further worsen cardiovascular complications. Therefore, the aim of the study was to investigate the haematological effects of oleanolic acid (OA) in streptozotocin- (STZ-) induced diabetic rats. Methods. The animals were separated into five groups; the nondiabetic group (ND), the diabetic control group (DC), and the treatment groups of insulin (170 μg/kg, s.c), metformin (500 mg/kg, p.o), and OA (80 mg/kg, p.o). OA was administered orally twice a day. Thereafter, the animals were sacrificed, and blood and tissues were collected for haematological, hormonal, and oxidative status analysis. Results. Untreated diabetic rats exhibited hyperglycaemia, elevated glycated haemoglobin (HbA1c), oxidative stress, and a reduced erythropoietin (EPO) concentration when compared to ND rats. However, administration of OA attenuated hyperglycaemia, HbA1c, and EPO concentrations compared to DC rats. The reduction of blood glucose concentration, HbA1c, and improved EPO concentrations was further associated with a notable increase in red blood cell (RBC) count and other RBC indices. We also observed an increase in the antioxidant status of the RBCs with a concomitant decrease in oxidative stress. Conclusion. These findings suggest that OA improves diabetes-induced haematological changes caused by hyperglycaemia and attenuates the progression of cardiovascular complications in DM individuals.